The Impact of Surgery on the Developmental Status of Late Preterm Infants – A Cohort Study - Amit Trivedi (Journal of Neonatal Surgery, 2015)
Aims: Despite increasing evidence in the literature regarding the impact of late prematurity on subsequent developmental impairment, the developmental outcome of late preterm infants who undergo major surgery remains unclear. The aim of this study therefore was to determine the developmental outcome for a cohort of late preterm surgical population.